DESIGN OF PLANTATION AREA OF PT PERTAMINA UBEP BLOCK LIMAU, SOUTH SUMATERA - Hadi, Akhmad Arifin; Candra Syah, Candra Syah (Jurnal Lanskap Indonesia, 2016)
ABSTRACTPT Pertamina UBEP Block Limau is an exploration state company located in Prabu-mulih city, South Sumatera Province. According to legal regulation, it is stated that PT Pertamina UBEP Limau has responsibility conserving biodiversity in exploration territory. The responsibility of its oil company showed by planting trees in open spaces inside the explorations areas. The trees planted are indigenous trees of Sumatera such as Meranti (Shorea sumatrana), Jelutung (Dyera lowii), Tembesu (Fragraea fragrans), Perupuk (Lopothepalum javanicum), Gaharu (Aquilaria malaccensis) and Pulai (Al-stonia scholaris). Those trees are used to be common plantation trees in South Su-matera but recently their number is become decreased as an impact of monoculture plantation. The only ex-situ trees planted are Jati Solomon (Tectona grandis Linn) as one of requirement from PT Pertamina UBEP Limau. The method for obtaining and processing data is descriptive method by site surveying. The base map was obtained from PT Pertamina UBEP Limau and it was updated with actual hidden under-ground utilities. According to the limitation of open spaces, the planting distance selected was 3x3 m square and the trees were arranged on non-utility open spaces inside exploration territory. According to the final planting plan, there were 10.850 trees planned to be planted on PT Pertamina UBEP Limau. The start of planting plan's implementation was held on August 2012 in Niru Field by planting 1.000 trees. In implementation activity, there are on field planting adjustments as a conse-quence of unrecorded underground utilities.Keywords: Planting Design, Plantation, South Sumatera